A Novel Technology for Processing Urban Waste Compost as a Fast-Releasing Nitrogen Source to Improve Soil Properties and Broccoli and Lettuce Production - de Nobile, Fabio Olivieri [UNESP]; Calero Hurtado, Alexander [UNESP]; Prado, Renato de Mello [UNESP]; de Souza, Henrique Antunes [UNESP]; Anunciação, Maria Gabriela [UNESP]; Palaretti, Luiz Fabiano [UNESP]; Dezem, Leticia Ane Sizuki Nociti [UNESP] (Springer Nature, 2021)
Purpose: This study evaluated nitrogen (N) mineralization dynamics in three soils after the addition of heat-treated urban waste amendments or urban waste compost (UWC). The effects of UWC and urea on soil properties and broccoli and lettuce production were compared. Methods: The first N mineralization experiment was conducted in a factorial arrangement (4 × 3), as a randomized complete block design (RCBD), with three replicates. Four UWC doses: 12.5, 25.0, 37.5, and 50.0 mg dm−3 were applied to three soils: sandy Ustoxic Quartzipsamment (QS), intermediate-texture red Ultisol (US), and clayey red Oxisol (OS), during eight incubation periods (0, 7, 14, 28, 42, 56, 70, and 84 days). In the second experiment, the effects of UWC and urea fertilizer on soil properties were compared. The growth of broccoli and lettuce plants was evaluated (experiments 3 and 4). The treatments (Experiments 2–4) followed a factorial arrangement (4 × 2; RCBD; three replicates), using OS soil. Four N doses (as for experiment 1) were combined with two N sources (UWC and urea). Results: The processed UWC application proportionally increased the N mineralization rate by 72% in QS, 54% in US, and 66% in OS. Furthermore, UWC application enhanced soil properties (pH and nutrient availability), compared with urea fertilizer, and improved N uptake, resulting in higher fresh biomass production in broccoli and lettuce plants (50.0 and 37.5 mg dm−3, respectively). Conclusions: Our findings suggest that heat-treated UWC is an economical, viable, and efficient fertilizer to improve soil properties and short-cycle vegetable crop productivity. Graphic Abstract: [Figure not available: see fulltext.]
Keywords: Brassica oleracea L; Domestic wastes; Lactuca sativa L; Nitrogen content; Organic fertilizer; Soil fertility